2017
DOI: 10.1021/acs.langmuir.7b02279
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Binding of Ethylene Oxide–Propylene Oxide Block Copolymers with Lipid Bilayers

Abstract: Block copolymers composed of poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO) have been widely used in cell membrane stabilization and permeabilization. To explore the mechanism of interaction between PPO-PEO block copolymers and lipid membranes, we have investigated how polymer structure influences the polymer-lipid bilayer association by varying the overall molecular weight, the hydrophobic and hydrophilic block lengths, and the endgroup structure systematically, using 1-palmitoyl-2-oleoyl-sn-glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(105 citation statements)
references
References 56 publications
6
98
1
Order By: Relevance
“…1A (without decanoic acid) is likely that decanoic acid solutions have a higher bulk viscosity than water (28). The slow set of coefficients is due to binding of amino acids to decanoic acid surfaces in accordance with other NMR diffusion results (29). This binding could be due to amino acids associating with the outer surface of vesicles and micelles (the structures of which appear in SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 77%
“…1A (without decanoic acid) is likely that decanoic acid solutions have a higher bulk viscosity than water (28). The slow set of coefficients is due to binding of amino acids to decanoic acid surfaces in accordance with other NMR diffusion results (29). This binding could be due to amino acids associating with the outer surface of vesicles and micelles (the structures of which appear in SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 77%
“…Fabrication of poloxamers involves the addition of ethylene oxide to polyoxypropylene glycol, which again is a product of the reaction between polyethylene glycol (PEG) and propylene oxide. These types of block polymers are reported to be more advantageous as stabilizers compare to traditional homopolymers 57 . Commonly used poloxamer in nanocrystals formulations is poloxamer 188 and (Pluronic ® F68) poloxamer 407 (Pluronic ® F127).…”
Section: Parenteral Nanosuspensionmentioning
confidence: 99%
“…Using this, they showed that the shorter copolymer had an effect only on the inner part of the bilayer while the longer one had an effect on both the interface and the inner part of the bilayer. By mixing POPC unilamellar liposomes with PEO-PPO copolymers of different block sizes and analyzing these mixtures with pulsed-field-gradient NMR, Zhang et al [167] quantified polymer diffusion in the absence and presence of liposomes. From their results, they could assess the binding of the polymers to the liposomes.…”
Section: Interactions With Model Membranesmentioning
confidence: 99%